Analisis Penerapan Hygiene dan Sanitasi Makanan pada Penjamah Makanan Jajanan Salome di Sekitar Taman Nostalgia Kota Kupang - Mega Silvia; Marylin S. Junias; Cathrin W.D. Geghi (Yayasan Literasi Sains Indonesia, 2023)
Unsafe food contains bacteria, viruses, parasites, harmful chemical substances causing more than 200 diseases. One of the causes of fundamental food sanitation problems is the characteristics of food handlers. Food handlers who do not have knowledge about good food processing methods have an impact on processed food. Indonesia's health profile in 2017 shows that the percentage of TPM eligible for health nationally in 2017 was 18.04%, an increase at the previous year of 13.66%. Eligible TPM continued to increase to 33.69% of the total 127,554, TPM in 2018. NTT Province has 237 (12.76%) TPM that meet health requirements out of a total of 1,857 TPM available. This study aims to determine the application of food hygiene and sanitation to salome snack food handlers around Nostalgia Park in Kupang City. This type of research is a descriptive quantitative conducted at Nostalgia Park in Kupang City starting in May 2023. The number of samples amounted to 17 respondents, with the sampling method being non-probability sampling with purposive sampling techniques. Data were analyzed univariately. The results showed that the application of food hygiene and sanitation with not good enough categories as many as 7 people (41.2%), 6 people (35.3%) had sufficient knowledge related to food hygiene and sanitation, 9 people (52.9%) had negative attitudes related to the implementation of food hygiene and sanitation, and as many as 11 people (64.7%) had poor facilities. It is recommended to the Health Office of Kupang City to carry out health promotion for salome snack food handlers around Taman Nostalgia to increase food handlers' awareness about food hygiene and sanitation.